2015
DOI: 10.1111/acem.12747
|View full text |Cite
|
Sign up to set email alerts
|

Designing Real‐time Decision Support for Trauma Resuscitations

Abstract: Background Use of electronic clinical decision support (eCDS) has been recommended to improve implementation of clinical decision rules. Many eCDS tools, however, are designed and implemented without taking into account the context in which clinical work is performed. Implementation of the pediatric traumatic brain injury (TBI) clinical decision rule at one Level I pediatric emergency department includes an electronic questionnaire triggered when ordering a head computed tomography using computerized physician… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 51 publications
(45 reference statements)
0
13
0
Order By: Relevance
“…We will observe each scenario until the team reaches a consensus about the diagnosis. Previous studies have observed 32 to 50 cases for reaching data saturation [43,45-47].…”
Section: Methodsmentioning
confidence: 99%
“…We will observe each scenario until the team reaches a consensus about the diagnosis. Previous studies have observed 32 to 50 cases for reaching data saturation [43,45-47].…”
Section: Methodsmentioning
confidence: 99%
“…Within health care settings, one of the most common reasons eHealth apps fail to effectively increase the health outcomes they are designed to aid and improve quality of care is incompatibility between the app and clinical workflow [ 1 - 7 ]—the series of tasks conducted to complete clinical care in what order and by whom. Incompatibilities often stem from a wait-and-see method of implementation common to many eHealth interventions whereby an intervention is introduced into a clinical setting and the clinical workflow either adjusts to accommodate or does not [ 8 , 9 ]. Frequently, a lack of integration with clinical workflow results in clinical staff creating work-arounds or adaptations that interfere with the core components of the intervention [ 2 - 4 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consider as well the potentially deleterious effect of the number of "clicks" that EPs working in an EHR-enabled environment face each shift [30]. Other work suggests that CDSSs are more effective if adapted based on human factor analysis [31]. While there has been significant backlash regarding the benefits of the EHR, we know that certain aspects of it are effective -these include well-designed assistive order sets and condition-specific decision support tools [18,32].…”
Section: Discussionmentioning
confidence: 99%